Evaluation of the Self-Help Housing Stimulant Assistance Program (BSPS) and Its Impact on Community Welfare in Kuranji District, Padang City - Nabila Siti Aqilah; Rahmadhona Fitri Helmi (The Future of Education Journal, 2026)
Housing is a basic human need that directly affects family welfare, yet many low income households in Indonesia still live in inadequate dwellings. The National Statistics Agency's 2024 report shows that only around 65 percent of Indonesian households occupy a proper house. This condition pushed the government to run the Housing Self Help Stimulant Assistance Program, known as BSPS, which helps low income families build or renovate their houses independently. This study aims to evaluate the implementation of BSPS toward community welfare in Kuranji Subdistrict, Padang City. The research applies a qualitative descriptive method, with data gathered through interviews, observation, and document review. Thirteen informants were selected through purposive and snowball sampling, consisting of beneficiaries, a field facilitator, staff of the Provincial Housing Unit, and a subdistrict officer. Data were analyzed using William N. Dunn's six evaluation criteria, namely effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. Findings show that BSPS brought real benefit by improving the physical condition of houses, making them safer and more comfortable. However, the program has not run optimally, since the assistance fund of twenty million rupiah is insufficient to cover rising material and labor costs, the beneficiary data still contains inaccuracies, and the quota provided cannot cover the number of substandard houses in the area. Communal land ownership issues also limit access for some eligible households. Overall, the program has a positive impact on housing quality, though improvements are needed in data accuracy, aid amount, and implementation mechanism to make it more effective and equitable.